Phenol and Nitrophenols in the Air and Dew Waters of Santiago de Chile - Lissi-Gervaso, E; Rubio-Campos, M (2012)
Phenol, nitrophenols and dinitrophenols were measured in air and dews in downtown Santiago de Chile. In both systems, phenol, 2-nitrophenol (2-NP), and 4-nitrophenol (4-NP) were the compounds found in higher concentrations and with major frequency. Temporal profiles in air were compatible with a significant direct incorporation from mobile sources. The data can be explained in terms of a faster removal of 2-NP than 4-NP, with the former predominating in fresh air masses and 4-NP in more aged samples. All these compounds, as well as dinitrophenols, were found in dew waters. Simultaneous measurements in air and dew indicate that phenol present in dew exceeds that expected in equilibrated samples, while the opposite occurs with 4-NP. This last result is associated to mass transfer limitations for the highly water soluble nitroderivative. © 2011 Elsevier Ltd.